Test of boiler and engine at flour mill of the Long Barner Milling Company - Ross, Donald (My University, 1907)
Introduction: The test was made on the boiler and engine at the flour mill of the Long-Barner Milling Company. The boiler was installed in a great hurry two years ago as the old one was worn out. It is eighteen feet long, seventy-two inches in diameter, and a total heating surface of 1539 square feet. There are thirty-three square feet of grate surface. The boiler was manufactured by Joseph Bromich, of Topeka, and installed in 1905. The fuel used was Weir City nut coal, some of the best that can be secured here for steaming purposes. A fresh car-load had just been received the week before, and was stored in a covered shed, so that there could be no deterioration by weathering. Power is transmitted by belts from a long engine shaft that runs through the engine room wall to the basement under the mill proper. Speed was taken with a revolution counter and stop watch from the inner end of this shaft. A heavy sixteen foot cast iron fly wheel is on this shaft in the engine room. The engine is of the plain slide valve type. It is a horizontal engine, manufactured by the Atlas Engine Company, and has been in almost continuous service in the basement of this mill for the past twenty-five years. It is rated as a seventy-five.horse power engine. The mechanical clearance in the head end is three-eighths of an inch, while the crank end has but three-sixteenths of an inch. The steam chest is placed…
Citation: Ross, Donald. Test of boiler and engine at flour mill of the Long Barner Milling Company. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Long Barner Milling Company; Boilers; Power Generation; Theses